Kolaborasi Triple Helix dalam Program Inovasi Desa: Mendorong Ekonomi Berbasis Pengetahuan di Desa Poka, Kota Ambon - Udiyasa, Ketut; Madubun, Jusuf (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Law Number 6 of 2014 on Villages (Undang-Undang Nomor 6 Tahun 2014 tentang Desa) establishes that villages play a central role in development, aiming to create self-sufficient and competitive communities. In this context, the Innovative Village Program (PDI) serves as a key strategy to enhance the effective use of village funds, develop local economic potential, and improve community welfare. This study examines the role of the Triple Helix model of collaboration in supporting innovation programs in Poka Village, Ambon City, to foster a knowledge-based economy. This research employs a qualitative method with a case study approach. Data collection was conducted through in-depth interviews, observations, and document analysis. The data were analyzed descriptively using triangulation techniques to enhance the validity of the findings. The results show that the Triple Helix collaboration, involving the village government, community, academics, and economic actors such as Village-Owned Enterprises (BUMDes) and Micro, Small, and Medium Enterprises (MSMEs), plays a crucial role in fostering innovation and accelerating technology adoption in Poka Village. The village government serves as a planner and facilitator, the village community acts as the primary driver of innovation, academics function as mentors and technology developers, while economic actors serve as users and managers of innovation outcomes. The uniqueness of this research lies in its collaborative approach to developing an innovation-driven village based on a knowledge economy. This study recommends enhancing community capacity through science and technology-based training, optimizing the role of academics in applying innovative technologies, and strengthening policies that promote synergy among actors within the Triple Helix model. These findings contribute to the advancement of social sciences and humanities, particularly in the study of innovation-driven rural development and multi-sectoral collaboration.